Singing Arc - Konstuktion av en tongenererande teslaspole - Poposki, Daniel; Marne, Michael; Höglund, Nils; Falk, George; Loftman, Victor; Blomkvist, Niklas (My University, 2017)
A muscial tesla coil is a form of transformer which at high frequency transforms a low primary voltage into a considerably higher secondary voltage that results in discharges. These discharges can be modulated into musical tones by turning on and off the tesla coil with the frequency of the tones. In order to construct a musical tesla coil with variable discharge rate a Dual Resonant Solid State Tesla Coil was created. The resonant frequency of the primary circuit was matched to the frequency of the secondary circuit, which was measured to 121kHz. This was achived by the usage of capacitors connected in series with the primary coil. The primary coil was shaped as a flat Archimedian spiral with the ability of frequency tuning by moving its variable connection point. The resonant frequency signal was generated by a Phase Locked Loop, which received the oscillation frequency from the tesla coil through an antenna and created a square wave with the same frequency. The resonant frequency was combined, through a network of AND-gates, with the tone signal from an Arduino, which in turn was controlled by a software client written in C#. The client decoded .midi-files into an array of tones whose frequency was sent to the Ardunio. The Arduino shut off and turned on the tesla coil with the same frequency as the tone and thus creating an audible tone. An H-bridge was utilized to create an AC-voltage using the control signal together with a DC-source. The ampacities of the H-bridge was however the limiting factor of the magnitude of the discharges which could be generated. At 100A through the primary coil, electrical discharges of 11.5cm in length could be generated which could play musical pieces.
Keywords: Elkraftteknik; Electric power engineering